Analysis Of Consumer Preferences For Marketing Communication Strategy On Sass And Co - Nadya Sukmaaji; Sisca Eka Fitria (Jurnal Ilmu Sosial Politik dan Humaniora (Jisora), 2018)
The development of the creative industrial sector is able to contribute significantly to the national economy, one of which is fashion business. This is due to the phenomenon of fashion trends that gave birth to many business actors in the field of the fashion business. With so many fashion business players, fashion business competition will be more competitive that can impact on business success. One strategy that can be taken by business actors is product development, but according to modern marketing, it takes more than developing a product. Business actors need to apply various forms of communication in marketing so as to effectively reach and influence target markets through marketing communications strategies. Consumer preferences can be used to help the selection of the right marketing communications strategy as an effort to grab attention and influence the target market effectively in order to increase sales resultsThis study aims to determine consumer preferences of marketing communication strategy for Sass and Co. products. This study uses five marketing communication mix as variables or attributes and 16 sub-attributes. Sampling was done by Non-Probability Sampling method with a total of 400 respondents and using conjoint analysis technique. The results of this study show that the best combination of respondents is the marketing communication strategy using social media advertising, sales promotion by giving discounts, direct marketing through Shopee, word of mouth marketing using friend recommendation, and using personal sales through the offline store.